2010
DOI: 10.1108/00220411011016380
|View full text |Cite
|
Sign up to set email alerts
|

Grounded theory in practice: issues and discussion for new qualitative researchers

Abstract: Purpose -The purpose of this paper is to clarify four common confusions in grounded theory (GT) use by demonstrating an example of the author's doctoral study into conceptualising higher education students' learning and knowledge sharing by exploring blogging phenomena. It seeks not only to present the author's personal experience and views, but also to shed light on the causes of the confusion for novice qualitative researchers. Design/methodology/approach -A review of literature on GT and the author's practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 36 publications
0
55
0
5
Order By: Relevance
“…These theories are considered to differ with respect levels of generality (Tan 2010) or conceptual abstraction (Urquhart et al 2010, Dey 2007. In this sense, substantive theories require comparative analysis "between or among groups within the same substantive area" (Dey 2007, p40) whereas formal theories draw from disparate groups within the same formal area.…”
Section: Introductionmentioning
confidence: 99%
“…These theories are considered to differ with respect levels of generality (Tan 2010) or conceptual abstraction (Urquhart et al 2010, Dey 2007. In this sense, substantive theories require comparative analysis "between or among groups within the same substantive area" (Dey 2007, p40) whereas formal theories draw from disparate groups within the same formal area.…”
Section: Introductionmentioning
confidence: 99%
“…Cette méthode est donc essentiellement l'inverse des approches traditionnelles qui consistent à vérifier des théories existantes (Tan, 2010).…”
Section: Pertinence De La Mte En Généralunclassified
“…The studies by Ellis, Vedi and Olaisen stem directly from their PhD research. Since then, numerous examples of the use of Grounded Theory in PhD research in the LIS field can be found, as referenced in Mansourian (2006) and Tan (2010).…”
Section: Introductionmentioning
confidence: 99%